Construction and validation of an instrument to assess the reading comprehension of students from the third to the fifth grades of elementary school - Cunha, Vera Lúcia Orlandi; Capellini, Simone Aparecida [UNESP] (Sociedade Brasileira de Fonoaudiologia, 2014)
Objetivo:Este estudo teve como objetivo construir e validar um instrumento de avaliação da compreensão de leitura a fim de caracterizar o perfil de leitura e detectar dificuldades de compreensão em escolares do terceiro ao quinto ano do Ensino Fundamental.Métodos:Participaram 378 escolares divididos em trés grupos para avaliação da compreensão de proposições literais e inferenciais de micro e macroestruturas de dois textos expositivos e dois textos narrativos por meio de questões de múltipla escolha.Resultados:Os dados analisados estatisticamente indicaram valores do teste alfa de Cronbach apresentando consisténcia interna nos quatros textos aplicados para os trés grupos.Conclusão:Foi possível constatar que os escolares apresentaram menor número de erros com o aumento da escolarização e que cada tipo de texto apresentou uma dificuldade específica para os escolares.

Purpose:In this study, we aimed at building and validating an instrument to assess reading comprehension, with the purpose of characterizing the reading profile and detecting comprehension difficulties among students from the third to the fifth grades of elementary school.Methods:Participants were 378 students, divided into three groups. Their comprehension of micro- and macrostructural literal and inferential propositions that composed two expository texts and two narrative texts were assessed by means of multiple-choice questions.Results:The data analyzed statistically yielded Cronbach's alpha values showing internal consistency in the four texts applied to the three groups.Conclusion:It was possible to verify that the students had fewer errors as the school years progressed and that each type of text posed a particular difficulty to the students.
Construção e validação de instrumento de avaliação da compreensão de leitura para escolares do terceiro ao quinto ano do Ensino Fundamental
Keywords: Leitura; Compreensão; Avaliação; Avaliação educacional; Escolaridade; Reading; Comprehension; Evaluation; Educational assessment; Schooling